Privacy Types - Majeed Mohamed Fareed Majeed (Randwick International of Education and Linguistics Science Journal, 2021)
The right to privacy is one of the most problematic rights. In the absence of any consensus on a clear theoretical basis for the concept of privacy; there is hardly a link, reliable, between the various issues and topics, which are included under this right. Privacy claims are used to defend rights that seem quite divergent, such as the right not to be monitored by phone calls, and the right to know what a telecom company keeps of personal data for its customers. The absence of a clear theoretical basis for the right to privacy is exacerbated by the fact that it is exposed to multiple dangers in the era of the massive expansion of the use of the Internet and the development of its applications. The actuality of material, described in the article, conditioned the urgent necessities of society simply to settle a question about privacy types and their appliance in the society. Theoretical and legal conversations about the relationship between taws and privacy were investigated in the article. This paper makes a contribution to a forward-looking privacy framework by examining the privacy impacts of six new and emerging technologies. It examines the privacy issues that each of these technologies present and contends that there are seven distinct sorts of privacy. This contextual investigation data propose that a loose conceptualization of privacy might be important to keep up a smoothness that empowers new measurements of privacy to be identified, that will be understood and addressed so as to adequately react to quick technological evolution.